Enhancing Students' Analyzing Skills on Reaction Rate Topics Using the Guided Inquiry Learning Model - Lubay, Olga Margareta; Fadiawati, Noor; Rosilawati, Ila (Universitas Lampung, 2024)
Abstract: Enhancing Students' Analyzing Skills on Reaction Rate Topics Using the Guided Inquiry Learning Model. This study aims to describe the effectiveness of the guided inquiry learning model on reaction rate material in improving analysis skills. The population in this study were all students in grade XI at SMA Negeri 13 Bandarlampung in the 2023/2024 academic year, using purposive sampling technique obtained grade XI 6 as the experimental class and grade XI 7 as the control class. This study used the matching only pretest and posttest control group design. The data obtained were analyzed by calculating the average n-gain score of the pretest and posttest analysis skills. Apart from that, hypothesis testing was also carried out using an independent t-test. The research results showed that the n-gain of analytical skills in the experimental class was in the high category, and the average posttest score for analytical skills in the experimental class was higher than in the control class. Based on the research results, it is concluded that the guided inquiry learning model on reaction rate material is effective in improving analyzing skills.Keywords: guided inquiry learning model, reaction rate, analyzing skills.DOI: 10.23960/jppk.v13.i1.2024.16